MIDDLEWARE PAYMENT GATEWAY ON THE DIGITAL CROWDFUNDING PLATFORM - M. Bima Surya; Irwan Alnarus Kautsar; Yulian Findawati; Suhendro Busono (Journal of Artificial Intelligence and Digital Economy, 2026)
Objective: This study aims to develop and implement a microservices-based payment gateway middleware integrated with web services to enhance transaction efficiency and reliability on crowdfunding platforms. Background: In the digital era, the demand for fast, secure, and efficient transaction systems has become increasingly critical, particularly in platforms handling large volumes of financial transactions. Traditional monolithic architectures often struggle to maintain scalability and flexibility, leading to potential bottlenecks and security risks. Method: The system was designed using a microservices architecture, allowing each payment-related process—such as authentication, transaction validation, and notification handling—to operate independently yet remain interconnected through APIs. Integration with web services ensures compatibility with various payment providers and crowdfunding systems. Findings: The implementation results demonstrate that the proposed middleware improves transaction processing speed, scalability, and fault tolerance compared to traditional models. Conclusion: The study concludes that adopting a microservices-based payment gateway middleware provides a sustainable solution for high-volume digital transactions, supporting the scalability, flexibility, and security required by modern crowdfunding ecosystems.